Physical activity levels of economically disadvantaged women living in the Olympic city of Rio de Janeiro. Issue 5 (3rd July 2016) - de Sousa-Mast, Fabiana R.; Reis, Arianne C.; Sperandei, Sandro; Gurgel, Luilma A.; Vieira, Marcelo C.; Pühse, Uwe
ABSTRACT: The objective of this study was to analyze the physical activity patterns of women living in a low-income community located in close proximity to the 2016 Rio de Janeiro Olympic Park. Data ( N = 140) were collected in June and July 2012 using the International Physical Activity Questionnaire. Findings indicated that the majority (54.8%) of participants reported high levels of physical activity. The domains that contributed the most to this pattern were occupational and household physical activity. Significantly, 88.1% of participants reported low physical activity levels during their leisure-time. In the transport-related domain, participants were relatively more active, but more than half of them (57%) spent less than 600 MET-minutes/week in this domain. The results highlighted the discrepancies between different physical activity domains. In addition, the findings also suggested that low-income women in our study engaged little in physical activity during their leisure time. Therefore, the proposed commitments found in the Rio de Janeiro Candidature File to host the 2016 Olympic Games to increase sport/physical activity participation within low-income communities in Rio de Janeiro need to be implemented effectively if this physical activity behavior during self-directed time is to be changed.